A Survey Qualitative Study: Factors on Promoting and Hindering of Foreign Students to Communicate English - Rizky Gushendra; Mira Ayu Defitri (Indonesian Journal of Integrated English Language Teaching, 2016)
The purpose of the study to investigate foreign students about the factors that influenced their willing to communicate English. The objectives of this research were to explain about the factors promote and factors hinder foreign students in using English. This research was administered at State Islamic University of Sultan Syarif Kasim Riau. The participants of this research were three foreign students and their classmates at State Islamic University of Sultan Syarif Kasim Riau. The researchers used purposive sampling to select the participants based on their judgment, then did some interviews to foreign students to triangulate into their classmates, which was used to confirm the information given by foreign students. Furthermore, the data were analyzed through reviewing, transcribing, coding and interpreting it. The data that had been collected through interviews were transcribed. Then, the data were matched and categorized into two categories. Finally, the result of analysis showed that both of the foreign students were influenced by language learning orientation, social influences, self-confidence, language anxiety and interlocutors as the factors promote and factors hinder underlying their willingness to communicate in English.